Retrofit em sortificador crossbelt - Travasso, Mayk Nunes (2021)
The work carried out, adresses a Retrofit in the Crossbelt Sortifier equipment, (Sorter), for a better understanding of the operational process of saparation of volumes and the problems in the equipment, details and data of sensors, motors and controllers will be presented, to assist in the decision and dimensioning of componentes, which will be presented in preventive maintenance format to the Automation sector.